PENGARUH PAJAK, RETRIBUSI DAN PENDAPATAN LAINLAIN YANG SAH TERHADAP PENDAPATAN DAERAHDI PEMERINTAH KABUPATEN TABANAN - Nyoman Ariana Guna,SE M.Agb; Drs I Dewa Gede Rastana. M.Agb; Dr I Wayan Mula Sarjana,SE, M.Si (Jurnal Ilmiah Satyagraha, 2023)
Many factors can affect regional income in the Tabanan Regency Government, one ofwhich is taxes, levies and other legitimate income, so in this study it will be examinedabout the effect of taxes, levies and other legitimate income on regional income in the Tabanan Regency Government. Based on data analysis, the results obtained (1) tax has a positive and significant effect partially on regional income in the Tabanan Regency Government, because the t-count value is greater than the t-table value (5.827 > 1.943) and the significance value is less than five percent (0.000 < 0.050 ), (2) retribution has a positive and significant effect partially on regional income in the Tabanan Regency Government, because the t-count value is greater than the t-table value (2.971 > 1.943) and thesignificance value is less than five percent (0.000 < 0.050), ( 3) Other legitimateincome has a positive and significant partial effect on regional income in the TabananRegency Government, because the t-count value is greater than the t-table value(3.846 > 1.943) and the significance value is less than five percent (0.042 < 0.050)and (4) taxes, levies and other legitimate income have a significant simultaneouseffect on regional income in the Taba Regency Government nan, because thecalculated F value is greater than the table F value (34.009 > 4.760).To the Tabanan Regency government given the importance of regional income incarrying out regional development, it is hoped that the Tabanan Regency governmentshould be able to optimize the potential of the region it has so that revenue fromtaxes, levies and other legitimate income can continue to increase in the future